Analysis Of Cancellation Of Land Rights Certificates In Certificate Overlapping Cases - Tiara Kusuma, Dhika; Gusti Ayu Ketut Rachmi Handayani , I; Karjoko, Lego (International Journal of Educational Research & Social Sciences, 2024)
This study aims to determine and analyze how the cancellation of a land title certificate due to an overlapping certificate. This case study examines Mataram State Administrative Court Decision No.54/G/2022/PTUN.MTR Jo. State Administrative High Court Decision No.25/B/2023/PTTUN.MTR uses the perspective of equitable legal certainty to find out and analyze the overlapping problems that are still often encountered in Indonesia. The problem of the research is the background of the occurrence of an overlapping certificate in Decision No.54/G/2022/PTUN.MTR and what implications arise against the disputed object land. The research method used is normative legal research using a case approach and using primary legal materials including Decision No.54/G/2022/PTUN.MTR on the occurrence of an overlapping certificate. The result of this research is that the certificate issued by the National Land Agency has been deemed defective and must be canceled so as not to harm the Plaintiff as the legitimate holder of the Certificate of Ownership with evidence in the form of a Sale and Purchase Letter between the Plaintiff's parents and the Defendant's parents.